The making and selling of post-Mao Beijing - Broudehoux, Anne-Marie (Planning, history, and the environment series., 2004)
"Describes the changing life of the city and its inhabitants during the final decades of the twentieth century and examines the complex forces at play in the search for modernity. The author presents us with four case studies of how the city is marketing and selling itself (including its refurbishment for the 2008 Olympic bid) and concludes that Beijing's urban image construction may provide an avenue for opposition groups to challenge the hegemony of those in power."--Publisher's description